Performance and mechanism of Mg/Fe layered double hydroxides for fluoride and arsenate removal from aqueous solution - Kang, Dongjuan; Yu, Xiaolin; Tong, Shengrui; Ge, Maofa; Zuo, Junchao; Cao, Changyan; Song, Weiguo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2013)
[Display omitted] •Mg/Fe-CLDH adsorbent was synthesized for simultaneous removal of F and As(V).•There was no competitive adsorption between F and As(V) on Mg/Fe-CLDH adsorbent.•Mg/Fe-CLDH adsorbent can achieve the simultaneous removal of F and As(V).•Effect of mixed oxides formed on adsorbent was more obvious than BET on adsorption.•Adsorption mechanisms of F and As(V) on Mg/Fe-CLDH were analyzed in detail. The present study evaluated calcined Mg/Fe layered double hydroxide (Mg/Fe-CLDH) as an adsorbent for simultaneous removal of fluoride and arsenate from aqueous solution. The Mg/Fe layered double hydroxide (Mg/Fe-LDH) was synthesized by co-precipitation method. A series of batch experiments were performed under various conditions, such as M2+/M3+ ratio, calcination temperature, initial anions concentrations, contact time, solution pH and competitive adsorption, for the adsorption of fluoride and arsenate on Mg/Fe-CLDH. It was found that the Mg/Fe-CLDH adsorbent with a M2+/M3+ ratio of 5, calcined at 400°C and pH 7, had the largest adsorption capacity of 50.91 and 50.24mg/g for fluoride and arsenate, respectively. Data of equilibrium experiments were fitted well to Langmuir isotherm model and pseudo-second-order kinetic model. Competitive adsorption experiments indicated that the Mg/Fe-CLDH adsorbents can achieve the simultaneous removal of fluoride and arsenate. The adsorbents were characterized by BET, SEM, XRD, FT-IR and XPS, and the analysis results demonstrated that the adsorption mechanism involved surface adsorption, ion exchange interaction and original LDH structure reconstruction by rehydration of mixed metal oxides and concomitant intercalation of fluoride and arsenate ions into the interlayer region.